Demonstration of acoustic waveguiding and tight bending in phononic crystals - Baboly, M. Ghasemi; Raza, A.; Brady, J.; Reinke, C. M.; Leseman, Zayd Chad; El-Kady, I. (My University, 2016)
The systematic design, fabrication, and characterization of an isolated, single-mode, 90 degrees bend phononic crystal (PnC) waveguide are presented. A PnC consisting of a 2D square array of circular air holes in an aluminum substrate is used, and waveguides are created by introducing a line defect in the PnC lattice. A high transmission coefficient is observed (-1 dB) for the straight sections of the waveguide, and an overall 2.3 dB transmission loss is observed (a transmission coefficient of 76%) for the 90 degrees bend. Further optimization of the structure may yield higher transmission efficiencies. This manuscript shows the complete design process for an engineered 90 degrees bend PnC waveguide from inception to experimental demonstration. Published by AIP Publishing.
Citation: Baboly, M. G., Raza, A., Brady, J., Reinke, C. M., Leseman, Z. C., & El-Kady, I. (2016). Demonstration of acoustic waveguiding and tight bending in phononic crystals. Applied Physics Letters, 109(18), 4. doi:10.1063/1.4966463
Keywords: Band-Structure; Photonic Crystal; Guides; Composites; Physics